Annual Plan 1970-71 - Planning Commission (Planning Commission, 1970)
The year 1969-70 carried forward the process of economic growth with a fair measure of success in many fields. The production of food grains is estimated to have increased to 100 million tonnes from 94 million tonnes during 1968-69. The output of some commercial crops, particularly sugarcane and raw jute also recorded sizeable increases. The rate of growth of industrial production improved further to around 7 per cent from 6.2 per cent achieved in 1968-69 though it fell short of the Annual Plan target of 8 per cent.
Government of India Planning Commission
Government of India Planning Commission